Surveillance and monitoring the cereal rust diseases in Lebanon, Morocco, and Tunisia in 2022 - Nazari, Kumarse; El Amil, Rola; Al-Jaboobi, Muamar; Maafa, Ilyass; Kemal, Seid Ahmed; Ramdani, Abdelhamid (2022)
Tracking the movement of the wheat rust pathogens and monitoring their pathogenic variabilities are the main pillars in successful breeding for durable rust resistance and disease management programs. Despite the severe drought conditions in wheat growing areas in CWANA in 2022, the rust surveillance was coordinated by the Regional Cereal Rust Research Center-Turkey in Lebanon, Morocco, and Tunisia, following the BGRI rust surveillance protocols. The national rust surveillance teams at the Lebanese Agricultural Research Institute, Institut National de la Recherche Agronomique (Morocco), and INSTITUT NATIONAL DES GRANDES CULTURES-TUNISIA (Tunisia) conducted the rust surveys in target countries. The GPS coordinates of survey sites, the status of rust diseases, and crop phenology were collected and shared with the online Global Cereal Rust Surveillance and Monitoring System (https://rusttracker.cimmyt.org) following the BGRI standard rust surveillance protocol (https://rusttracker.cimmyt.org/wp-content/uploads/2011/11/2013-Updated-BGRI-protocols-v2-web.pdf).